2003
DOI: 10.1081/ncn-120021971
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Triple Helices Formed by Oligonucleotides Containing 8-Aminopurines

Abstract: The synthesis of parallel hairpins carrying 8-aminopurines is described. These hairpins have a high affinity for specific polypyrimidine sequences resulting in the formation of very stable triplexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 8 publications
2
32
0
Order By: Relevance
“…The synthesis of oligonucleotides carrying alkynyl and the synthesis of oligonucleotides carrying azido groups were carried out using three methods. We have demonstrated that the 5'-ends of two oligonucleotides can be chemically linked using a Cu- Oligonucleotides with a parallel duplex structure with 5'-5' linkages are of interest for their triplex-forming properties [19][20][21][22]. The synthesis of these compounds by the linking of two parts is a considerable challenge.…”
Section: Cu-catalyzed Cycloaddition Of Azido-oligonucleotides and Alkmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of oligonucleotides carrying alkynyl and the synthesis of oligonucleotides carrying azido groups were carried out using three methods. We have demonstrated that the 5'-ends of two oligonucleotides can be chemically linked using a Cu- Oligonucleotides with a parallel duplex structure with 5'-5' linkages are of interest for their triplex-forming properties [19][20][21][22]. The synthesis of these compounds by the linking of two parts is a considerable challenge.…”
Section: Cu-catalyzed Cycloaddition Of Azido-oligonucleotides and Alkmentioning
confidence: 99%
“…If half of the hairpin is a polypurine sequence and the other half is a polypyrimidine sequence, the resulting parallel-stranded duplex will bind a polypyrimidine sequence by triple helix formation [20][21][22]. Our group has been especially interested in this type of oligonucleotides but until now the standard method for the preparation of parallelstranded duplexes has required the use of reversed phosphoramidites which are less efficient and more expensive [20][21][22]. The present study seeks to identify the optimal conditions for preparing parallel-stranded clamps.…”
mentioning
confidence: 99%
“…We have also run melting experiments in buffers containing NaCl and KCl instead of MgCl 2 in order to check whether G-quartet structures may inhibit triplex formation [24] but only a 8ºC decrease on Tm was observed (similar to parallel triplexes [15]) indicating no interference of these structures on triplex formation (data not shown).…”
Section: Melting Experimentsmentioning
confidence: 99%
“…The target polypyrimidine sequence was selected from a triplex studied by Xodo et al [13,14]. The same sequence has been 4 used to characterize the binding properties of both parallel [15] and antiparallel hairpins [16] (Scheme 2). We selected one of the phosphates in the middle of the Watson-Crick oligopurine sequence to disconnect the cyclic oligonucleotide (indicated in bold in Scheme 2) and design the sequence of the linear precursors.…”
mentioning
confidence: 99%
“…The parallel hairpin 2 ( Table 1) was prepared using standard phosphoramidites for the purine strand and reversed phosphoramidites for the assembly of the loop and the pyrimidine strand [25]. The overall yield was 70 % and the desired conjugate was isolated from truncated sequences by HPLC using trityl-on and trityl-off protocols.…”
mentioning
confidence: 99%